MONITORING OF FOLIAR DISEASES AND INSECT PESTS OF POTATO AT DIFFERENT DATES OF SOWING AND THEIR IMPACT ON TUBER YIELD IN HARYANA - Lakra, B S. (Potato Journal, 2013)
Potatoes are vulnerable to a large number of foliar diseases and insect pests which are responsible for huge damages and yield losses. A field trial was conducted for monitoring diseases and insect pests in 1 Oct., 16 Oct., 1 Nov., 16 Nov. and 1 Dec. planted crops from 2001-02 to 2004-05. In October sown crops, yield loss were highest due to occurrence of high incidence of apical leaf curl, white flies and jassids. November sown crops exhibited moderate level of all diseases and insect pests incurring only 15.0-20.0% yield loss. In December planted crops, early blight, leaf roll, severe mosaic and aphids, acquired serious proportions causing higher yield loss (30.0%). Monitoring of diseases and insect pests can help obtaining best fit time of planting which may save considerable yield losses without unnessesary pesticide application.